1 :\widehat{tOy}=\frac{1}{2}m° vì Ot là tia phân giác của \widehat{xOy}2 : \widehat{t'Oy}=\frac{1}{2}(180°-m°) vì Ot' là tia phân giác của \widehat{yOx'}3: \widehat{tOt'}=90° vì Ot vuông góc vớiOt'4:\widehat{x'Oy}=180°-m° vì \widehat{xOy} kề bù với \widehat{x'Oy}\Rightarrow trình tự định lí là : 4;1;2;3
1 :\widehat{tOy}=\frac{1}{2}m° vì
Ot là tia phân giác của
\widehat{xOy}2 :
\widehat{t'Oy}=\frac{1}{2}(180°-m°) vì
Ot' là tia phân giác của
\widehat{yOx'}3: \widehat{tOt'}=90° vì
Ot vuông góc với
Ot'4:\widehat{x'Oy}=180°-m° vì
\widehat{xOy} kề bù với
\widehat{x'Oy}\Rightarrow trình tự định lí là :
4;1;2;3